Scattering and Attenuations of Seismic Waves, Part I 1988
DOI: 10.1007/978-3-0348-7722-0_22
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Compressional Waves in Peridotite Measured as a Function of Temperature at 200 MPa

Abstract: Abstract--A technique has been developed to determine attenuation in rocks at high temperature using a gas-media, high-pressure apparatus. A pulse transmission technique and a spectral ratio method are used to study compressional seismic properties of rocks. Seismic waves are transmitted to and from the sample through buffer rods of mullite. The effect of seismic wave reflections within the sample assembly are cancelled out by taking ratios of the spectra measured at different temperatures. In order to obtain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

1991
1991
2002
2002

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 45 publications
1
17
1
Order By: Relevance
“…These values seem incompatible with the results of Sato et al [1988. The results obtained for peridotite at 0.2 GPa, a pressure that corresponds very closely to that at the Moho, predict Qp -6 at the solidus and suggest that the values obtained for the longest range paths require temperatures 200-300* below the solidus.…”
Section: Constraints On the Temperature And Melt Concentration Beneatcontrasting
confidence: 56%
See 2 more Smart Citations
“…These values seem incompatible with the results of Sato et al [1988. The results obtained for peridotite at 0.2 GPa, a pressure that corresponds very closely to that at the Moho, predict Qp -6 at the solidus and suggest that the values obtained for the longest range paths require temperatures 200-300* below the solidus.…”
Section: Constraints On the Temperature And Melt Concentration Beneatcontrasting
confidence: 56%
“…Obtaining measurements that are valid for both the compositional, pressure, and temperature conditions in the Earth and for the frequency, scale, and strain rates of seismic observations is a formidable task [e.g., Jackson, 1986;Christensen and Wepfer, 1989]. A number of measurements have been carried out on mafic and ultramafic samples at elevated temperatures [Woirguard and Gueguen, 1978;Berckhemer et al, 1979;Sacks and Murase, 1983;Kampfmann and Berckhemer, 1985;Sato and Manghnani, 1985;Manghnani et al, 1986;Sato et al, 1988Gueguen et al, 1989;Jackson et al, 1992]. The majority of these works were motivated by a desire to understand the properties of the asthenosphere and are thus primarily devoted to ultramafic samples.…”
Section: Laboratory Determinations Of Q At High Temperatures In Maficmentioning
confidence: 99%
See 1 more Smart Citation
“…Shear wave velocities outside the sill were assumed to be equal to Vp/V3" (i.e., surrounding rock was modeled as a Poisson solid). Sato et al, 1988Sato et al, , 1989 to 10 [ Murase and McBirney, 1973;Sato and Manghnani, 1985;Manghnani et al, 1986], but these measurements were made at high frequencies (>100 kHz) and may overpredict attenuation of lower-frequency (10 Hz) seismic energy. Wilcock et al…”
Section: Model Parametersmentioning
confidence: 99%
“…By means of a self-consistent correction method (Yoneda, 1990) 43, No. 4, 1995 (to 1,280•Ž) using a gas-media high-pressure apparatus (to 0.73GPa) (Sato et al, 1988b(Sato et al, , 1989b (Kjartansson, 1979;Lienert and Manghnani, 1990). The model of grain boundary relaxation suggested that an appropriate choice of grain size may give an ultrasonic Q that is applicable to the earth (Sato et al, 1989b).…”
mentioning
confidence: 99%